Integrated immunoassay-based broad detection of multi-class mycotoxins - Shupeng Yang (Taylor & Francis Group, 2018)
Europium (Eu3+) and horse radish peroxidase (HRP) are highly promising biosensors due to its excellent physical and chemical properties. The two biosensors are widely applied in time-resolved fluoroimmunoassay (TRFIA) and chemiluminescence enzyme-linked immunosorbent assay, respectively. In this work, the two technologies were integrated with parallel input and parallel output (PI–PO) characters. Eu3+ was adopted as probe I in TRFIA for deoxynivalenol and de-epoxyldexoylnivalenol with a limit of detection (LOD) of 4.74 and 4.56 ng/mL, while HRP was performed as probe II in CL-ELISA for FB1 with an LOD of 0.088 ng/mL. Compared to the traditional individual assay, this method exhibited fast and broad detection characteristics by integrating two immunoassays into one.